IMPLEMENTASI STANDAR GREEN KEY PADA KITCHEN DEPARTMENT DALAM MENDUKUNG PRAKTIK PERHOTELAN BERKELANJUTAN - Putri Amelia Ningsih; Nila Sartika Achmadi; Anggun Sari Sasmita; Dewi Andriani (HOME : Hospitality and Gastronomy Research Journal, 2026)
The hospitality industry plays an important role in supporting sustainable tourism development through the implementation of environmentally responsible operational practices. One form of sustainability implementation in the hotel sector is the Green Key program, an international environmental certification that promotes responsible hotel management. This study aims to analyze the implementation of Green Key standards in the Kitchen Department of Novotel Makassar Grand Shayla Hotel. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Informants were selected purposively based on their involvement in the Green Key program. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Green Key implementation in the Kitchen Department has been carried out through various sustainability practices, including food waste management, waste segregation, monitoring of water and energy consumption, the use of environmentally friendly cleaning products, the provision of vegetarian menu options, and the utilization of a hydroponic garden as part of the hotel's environmental initiatives. Staff engagement is also supported through training programs and sustainability-related information dissemination. However, challenges remain in fully verifying environmentally friendly raw materials and implementing renewable energy sources. Overall, the implementation of Green Key in the Kitchen Department has been effectively carried out and demonstrates the hotel's commitment to sustainable hospitality practices. Keywords: Green Key, sustainability, kitchen department, hotel, sustainable hospitality